Automatic Visualization of Relational Logic Models - Rayside, Derek; Chang, Felix; Dennis, Greg; Seater, Robert; Jackson, Daniel (Electronic Communications of the EASST, 2007)
Abstract: The Alloy Analyzer is a software design tool that generates examples of system states and executions from logic models and displays those examples graphically with a visualization facility. Although many users find the visualization indispensable, others are put off by the perceived difficulty of customizing the visualization and the poor quality of default diagrams. Many others do not take full advantage of the customization, usually because they do not understand what customizations are available and how best to apply them. This paper describes techniques for inferring a better initial customization, or theme, entirely automatically, based on the model and on criteria derived from experience with manual customization. A plugin that implements these techniques was applied to a repertoire of models. Each automatically generated theme was compared to an "expert" theme and to the default theme, with a simple metric that quantifies the visual difference between themes. These comparisons, which provide an indication of how closely the plugin can match the expert result, show the generated theme to be superior to the default for most models.